Calculation of Open Profile Thin-Walled Rod Systems Strengthened Under Load in Elastic and Plastic Deformations - M.N. Serazutdinov; M.N. Ubaydulloyev (Учёные записки Казанского университета: Серия Физико-математические науки)
This paper presents a variational method for calculation of open profile thin-walled rod systems strengthened under load. The main relations of the method are described. The principal feature of the method is that it is based on the use of deformation components for a straightline strip and also applicable for determining the stress-strain state of rods, the longitudinal axis and median line of cross-sectional profile of which consist of both straight-line and curved sections. Calculation results of the stress-strain state of thin-walled strengthened rod in elastic and elastic-plastic deformations are discussed.